Vaccination Take-up and Health: Evidence from a Flu Vaccination Program for the Elderly - Ylenia Brilli; Claudio Lucifora; Antonio Russo; Marco Tonello (Institute of Labor Economics (IZA), 2020)
We analyze the effects of a vaccination program providing free flu vaccine to individuals aged 65 or more on take-up behavior and hospitalization. Using both administrative and survey data, we implement a regression discontinuity design around the threshold at age 65, and find that the effect of the program on take-up ranges between 70% and 90% of the average vaccination rate for individuals aged less than 65. We show that this effect is not entirely driven by an income channel, but also depends on the expected benefits of vaccination. The analysis on health outcomes shows that the program reduces the likelihood of emergency hospitalization.
Keywords: I12; I18; J10; 330; public health; influenza; vaccination; health prevention policies